Educational, psychological, and behavioral considerations in niche online communities - Venkatesh, Vivek, 1976-; Wallin, Jason J., 1975-; Castro, Juan Carlos; Lewis, Jason Edward; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2014)
"This book examines the presence of online communities centered around niche topics of interest and the impact of these virtual spaces on community members, offering perspectives from interdisciplinary fields such as sociology, psychology, and education"--Provided by publisher.
The art of gaming: knowledge construction in visual culture learning communities / Kerry Freedman -- Gleaning strategies for knowledge sharing and collective assessment in the art classroom from the videogame, "Little Big Planet's Creator Spotlights" / Renee Jackson, William Robinson, Bart Simon -- Informal visual networks / Emiel Heijnen -- Constructing quilts, online communities, and quilter legacies: a narrative case study / Jessica Haak -- Niche and community online: artists' tactical media activities as pedagogy / Patti Pente -- Levelling (up) the playing field: how feminist gamers self-identify and learn in online communities / Sarmista Das -- Gendered subjectivities and cyberspace dialogues in lebanon: a critical discourse analysis / Jihan Rabah -- Women milbloggers: narratives of military life / Svetlana Makeyeva -- Re-envisioning a heroine's journey: three women in fandom / Marjorie Cohee Manifold -- Citizenship @ the edge of two worlds: the connection between theories of citizenship education and the study of niche online communities / Robert McGray, Tieja Thomas -- Social presence in online dissertation classes / Libi Shen, Irene Linlin Chen -- Ratchet head pedagogy: a narrative autobiographical inquiry about how we learned to customize and tune Italian motorcycles through asynchronous online discussion / Ann-Louise Davidson, Sylvain Durocher -- Citizen in/action: analyzing online forums for pedagogical insight / Tieja Thomas, Nicole Fournier-Sylvester, Vivek Venkatesh -- Technology stewarding as a medium to develop and sustain niche online communities / Ann-Louise Davidson, Issa Gulka, Andre Valle, Chantal Castonguay -- The process of weeding out: rhizome, rhizomes, and rhizomatic new media art communities / Robert W. Sweeny -- Some people aren't people on the inside: online connectivity and otherkin subjectivities / Margaret Shane -- The online community of second life and the residents of virtual ability island / Antonia Tzemopoulos -- Becoming anonymous: a politics of masking / Maria-Carolina Cambre -- Unauthorized comic book scanners / Darren Wershler, Kalervo Sinervo, Shannon Tien -- Perceptions of identity and expertise in heavy metal fans within one online community of practice / Kathryn Urbaniak -- From pride to prejudice to shame: multiple facets of the black metal scene within and without online environments / Vivek Venkatesh, Jeffrey S. Podoshen, David Perri, Kathryn Urbaniak -- The dark ecology of black metal / Jason J. Wallin -- Postscript: reflections on black metal "community" in the online context / Jason Netherton -- Conclusion: the code we learn with / Juan Carlos Castro.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF title page (viewed on 01/22/2014).
Keywords: Non-formal education; Educational innovations; Online social networks; Internet -- Social aspects; Internet in education; Computer-mediated communication; Cyber behavior; Digital leadership; Leadership in online communities; Niche online communities; Online identity; Virtual learning environments; Virtual subcultures; Electronic books